MgaSpn and H-NS: Two Unrelated Global Regulators with Similar DNA-Binding Properties - Solano-Collado, Virtu; Hüttener, Mário; Espinosa, Manuel; Juárez, Antonio; Bravo, Alicia (Frontiers in Molecular Biosciences, 2016)
Global regulators play an essential role in the adaptation of bacterial cells to specific niches. Bacterial pathogens thriving in the tissues and organs of their eukaryotic hosts are a well-studied example. Some of the proteins that recognize local DNA structures rather than specific nucleotide sequences act as global modulators in many bacteria, both Gram-negative and -positive. To this class of regulators belong the H-NS-like proteins, mainly identified in γ-Proteobacteria, and the MgaSpn-like proteins identified in Firmicutes. H-NS and MgaSpn from Escherichia coli and Streptococcus pneumoniae, respectively, neither have sequence similarity nor share structural domains. Nevertheless, they display common features in their interaction with DNA, namely: (i) they bind to DNA in a non-sequence-specific manner, (ii) they have a preference for intrinsically curved DNA regions, and (iii) they are able to form multimeric complexes on linear DNA. Using DNA fragments from the hemolysin operon regulatory region of the E. coli plasmid pHly152, we show in this work that MgaSpn is able to recognize particular regions on extended H-NS binding sites. Such regions are either located at or flanked by regions of potential bendability. Moreover, we show that the regulatory region of the pneumococcal P1623B promoter, which is recognized by MgaSpn, contains DNA motifs that are recognized by H-NS. These motifs are adjacent to regions of potential bendability. Our results suggest that both regulatory proteins recognize similar structural characteristics of DNA.